The perceptions of teachers related to the qualities they have (sample of Elazı? city) - Yeşilyurt, Etem (T.C. Milli Egitim Bakanligi, 2009)
In this paper, which is in a descriptive scanning model, it is aimed to determine the qualities that today's teachers have. The population of this studyconsists of teachers of secondary education which was working in Elazi{dotless}? citycenter in 2006-2007 academic years. A sample of 320 teachers was selected from this population randomly. Data, which were collected through the questionnaire,were analyzed and interpreted by frequencies, descriptive statistics, varianceanalysis and T-Test methods. As a result of this study, it has been determined that today's teachers have these perceptions considerably related to their qualities: sustaining the quality of teaching in a high level, self improvement, following the changes and innovations, taking measures for the safety of school andclassroom, instilling students ethical values of the society, presenting national and universal values, providing individual support, guiding, modeling, makingstudents to acquire national consciousness and making students to be acquainted with the harmful substances. Besides, there were meaningful differences among teachers' perceptions about their qualities according to some variables such as; school type, branch, and professional tenure.
Ö?retmenleri?n sahi?p olduklari Ni?teli?klere yöneli?k algilari (Elazi? i?li? örne?i?)
Keywords: Teacher; Teacher characters; Teacher peculiarities; Teacher qualities